Phytosterols and their derivatives: Potential health‐promoting uses against lipid metabolism and associated diseases, mechanism, and safety issues. Issue 4 (22nd June 2020) - Feng, Simin; Belwal, Tarun; Li, Li; Limwachiranon, Jarukitt; Liu, Xingquan; Luo, Zisheng
Abstract: Consumption of phytosterols (PSs), the plant‐based analogs of cholesterol, can reduce serum cholesterol levels. This review discusses the current state of the art into the research of the structural features and dietary sources of PSs and their derivatives. The effect of PSs on individual lipid metabolites is summarized in the present review. PS‐related nonalcoholic fatty liver disease (NAFLD), obesity, and the alleviation of inflammatory bowel diseases are discussed. PSs reduce the risk of having NAFLD by improving the blood biochemical parameters related to lipid transport and metabolism. However, current research on the circulating PSs indicates its safety concern regarding fatty liver disease induction. In addition, PS oxidation products exhibit pro‐atherogenic properties, cytotoxicity oxidative stress, apoptosis, and pro‐inflammatory properties. Further research is needed to investigate the bioavailability and safety issues of PSs and their derivatives in animal models and clinical trials.